Confessions of a D.C. madame : the politics of sex, lies & blackmail - Vinson, Henry W. (Trine Day, 2013)
A firsthand account of how public officials and other well-connected individuals have been compromised or blackmailed by their sexual improprieties, Confessions of a D.C. Madame relates the author's time running the largest gay escort service in Washington, DC, and his interactions with VIPs from government, business, and the media who solicited the escorts he employed. The book details the federal government's pernicious campaign waged against the author to ensure his silence and how he withstood relentless, fabricated attacks by the government, which included incarceration rooted in trumped up charges and outright lies. This fascinating and shocking facet of government malfeasance reveals the integral role blackmail plays in American politics and the unbelievable lengths the government perpetrates to silence those in the know.